SLIP HANDLING ON CONVEYORS TO EXTEND THE LIFE OF CONVEYORS AT THE DEPARTURES TERMINAL - Arka Alrora Harahap; Ni Putu Heni Handayani (Journal of Airport Engineering Technology (JAET), 2023)
The departure terminal’s Abdulrachman Saleh Malang Airport has facilities as an improvement in services for airplane passengers, such as aviobridges, escalators, travelators, elevators, and conveyors. Conveyors are mechanical systems that transfer luggage considerably from one location to another. To facilitate routing procedures, an effective model for conveyor operations must be developed, as well as the maintenance operation. This study aims to determine the consequences of lack of maintenance on the conveyor belt, namely the occurrence of slack in the belt so that it continues to experience abrasions on the sides of the conveyor and tears on the edges of the belt. The tear causes the fibers to unravel so that slip occurs between the belt and the upper idler shaft (carry idler) so that the idler cannot rotate. This causes the conveyor belt to run and malfunction. This research uses a qualitative method of conducting an exploratory study of the conveyor belt using experimental description research by describing and analyzing the existing conditions on the conveyor. The result is that there are belt fibers that cause slippage on the conveyor. Handling that can be done is cutting the fiber belt. The conclusion is that many factors can cause slippage on the conveyor belt, such as too heavy a load, old belt age, and the distance between the collecting belt conveyor and the transfer line conveyor. Maintenance can be done on the equipment to avoid slippage on the conveyor. Conveyor maintenance activities consist of two types, namely unplanned maintenance and planned maintenance. Unplanned maintenance is also called reactive maintenance or emergency maintenance.